Post-metaphysical thinking and religion: Practical reason, solidarity and the dialogue between philosophy and religion as a political task - Kaltsas, Spyridon (The Greek Review of Social Research, 2017)
In my paper I develop a critical account of Habermas’s recent turn to religion in the theoretical context determined by the concept of post-secular society. In my view the dialogue between post-metaphysical thinking and religion has to be understood as a political task. More specifically this dialogue aims to the reevaluation and extension of practical reason’s normative claims and has to be conceived as a response to the uncontrolled modernization which undermines social solidarity and leaves no place for the autonomy of practical reason. Furthermore I outline a critique of Habermas’s main theoretical strategy in regard to the problem of motivation of practical reason and the question of mediation between theory and praxis in the context of a critical theory of society.